CHRISTENDOM'S BULWARK: CROATIAN IDENTITY AND THE RESPONSE TO THE OTTOMAN ADVANCE, FIFTEENTH TO SIXTEENTH CENTURIES. (24th October 2014) - Housley, Norman
ABSTRACT: Croatia's entry to the EU in July 2013 signalled an association with Europe which was anticipated in the fifteenth and early sixteenth centuries in the regular use of antemurale (bulwark) rhetoric. This rhetoric was one of the salient characteristics of the period's crusading discourse, as the task of mobilising Christian assistance for regions confronting the Ottoman advance, and in so doing defending the faith as a whole, created a two-way traffic of information and arguments between the embattled frontline states and centres of power in the European interior. This paper investigates the distinctively Croatian features of antemurale language. The exposition of Croatia's role as an antemurale reveals the extent of the country's embrace of humanist ideals and techniques, enabling prominent lobbyists like Tomaso Negri to convey Croatia's plight with finesse in orations delivered at Rome, Venice and elsewhere. The written output of the humanists also shows that Croatia's dismemberment occurred at a time when national identity was forming, and the emphasis placed on the country's relationship with fellow-Catholics reinforced the tendency to look westwards. In addition, Croatia provides a telling example of the tension between centre and periphery in the person of Andrija Jamometić. When he dramatically called for the deposition of Sixtus IV in 1482, Jamometić included neglect of the crusade against the Turks amongst the accusations directed against the pope.